RELIGIUSITAS, KECERDASAN EMOSIONAL DAN KENAKALAN REMAJA - Lidya Sayidatun Nisya; Diah Sofiah (Jurnal Psikologi Tabularasa, 2012)
Abstract This research aims to find out the relationship of religiosity and emotional intelligence with juvenile delinquency. Subject of research is the students who sit in class VIII SMP Negeri 1 Kediri. The population was 997 people research but researchers only took a sample of 99 people. Research data collected by using the tools in the form of three scale corresponds to the number of variables is to study the scale of religiosity, emotional intelligence scale and the scale of juvenile delinquency. Of 99 pieces of the scale has been dispensed so as much as 86 pieces of the back. After checking the feasibility of such a scale, then the test is done by using correlation program SPSS version 16. The results showed that there is no relationship between religiosity and juvenile delinquency. Similarly, there is no relationship between emotional intelligence dan juvenile delinquency. Keywords: religiosity, emotional intelligence, juvenile delinquency